Genetic Variations of CD40 and LTβR Genes Are Associated With Increased Susceptibility and Clinical Outcome of Non-Small-Cell Carcinoma Patients - Dimitrakopoulos, Foteinos-Ioannis D.; Antonacopoulou, Anna G.; Kottorou, Anastasia E.; Kalofonou, Melpomeni; Panagopoulos, Nikolaos; Dougenis, Dimitrios; Makatsoris, Thomas; Tzelepi, Vasiliki; Koutras, Angelos; Kalofonos, Haralabos P. (Frontiers in Oncology, 2021)
Background: Immune system-related receptors CD40 (Tumor Necrosis Factor Receptor Superfamily Member 5), BAFFR (Tumor Necrosis Factor Receptor Superfamily Member 13C) and LTβR (Tumor Necrosis Factor Receptor Superfamily Member 3) play a pivotal role in non-small-cell lung cancer (NSCLC). To further evaluate their role in NSCLC, CD40 rs1883832 (T>C), BAFFR rs7290134 (A>G) and LTβR rs10849448 (A>G) SNPs were investigated regarding their impact in risk and clinical outcome of NSCLC patients. Methods: The three selected SNPs were evaluated in 229 NSCLC patients and 299 healthy controls, while CD40, BAFFR and LTβR protein expression were studied by immunohistochemistry in 96 tumor specimens from NSCLC patients. Results: In total, CD40 rs1883832 was associated with NSCLC risk, with T allele, after adjusting for co-factors, being related to increased risk (P=0.007; OR 1.701). Moreover, CT genotype was associated with increased risk (P=0.024; OR 1.606) and poorer five-year overall survival (OS) after adjusting for co-factors (P=0.001, HR 1.829), while CC was associated with higher CD40 expression in tumorous cells (P=0.040) and in stromal cells (P=0.036). In addition, AA homozygotes for the LTβR rs10849448 had increased risk for NSCLC in multivariate analysis (P=0.008; OR, 2.106) and higher LTβR membranous expression (P=0.035). Although BAFFR rs7290134 was associated with BAFFR membranous expression (P=0.039), BAFFR rs7290134 was not associated with neither the disease risk, nor the prognosis of NSCLC patients. Conclusions: In conclusion, CD40 rs1883832 and LTβR rs10849448 seem to be associated with increased risk for NSCLC, while CD40 rs1883832 is also associated with OS of patients with NSCLC.